Luminescent EVA (ethylene vinyl acetate) material as well as preparation method and application thereof

By using modified phosphor in the bath pillow material, combined with cooling shaping foaming technology in a magnetic environment, the problem of the difficulty of uniform distribution of phosphor in the bath pillow is solved, achieving more efficient luminous effect and better moisture and heat resistance.

CN119570149APending Publication Date: 2025-03-07FOSHAN LANGDI SANITARY WARE TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746512.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing luminescent bath pillow materials, it is difficult to evenly distribute the phosphor inside the bath pillow, which makes it difficult for the phosphor to absorb external energy and excite it during the luminescence process, resulting in waste of phosphor material.

Method used

Modified phosphor is adopted, which includes a magnetic fluorescent matrix and a lubricating layer coated on the surface of the fluorescent matrix. Through cooling and shaping foaming technology in a magnetic environment, the modified phosphor is uniformly distributed in the foaming material.

Benefits of technology

Modified phosphor can be evenly distributed on the surface of foamed material in a magnetic environment, improving luminous efficiency, reducing material waste, and improving the moisture and heat aging resistance of the bath pillow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164361460000121
    Figure BDA0005164361460000121
  • Figure BDA0005164361460000131
    Figure BDA0005164361460000131
Patent Text Reader

Abstract

The invention provides a luminous EVA (Ethylene Vinyl Acetate) material as well as a preparation method and application thereof, and relates to the technical field of foaming materials. According to the EVA material provided by the invention, an ethylene-vinyl acetate copolymer mixture is prepared from the following components in parts by mass: 70 to 80 parts of ethylene-vinyl acetate, 5 to 10 parts of a foaming agent, 1 to 3 parts of a cross-linking agent, 0.5 to 1 part of an accelerant and 5 to 10 parts of modified fluorescent powder; the modified fluorescent powder comprises a magnetic fluorescent matrix and a lubricating layer coated on the surface of the fluorescent matrix, and the magnetic fluorescent matrix comprises fluorescent powder and magnetic powder. The bath pillow has good moisture resistance in a humid environment, meanwhile, waste of the fluorescent powder can be avoided, and the use durability of the fluorescent powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a luminous EVA material and a preparation method and application thereof. Background Art

[0002] In modern fast-paced life, people pay more and more attention to the quality of life and personal enjoyment. Bathing is one of the important ways to relax in daily life, and various comfortable bathing products are constantly emerging. When people take a bath in the bathtub, leaning their necks on the bath pillow can provide sufficient support for people, while protecting the health of their cervical spine during the bathing process. The commonly used bath pillow materials are mainly made of ethylene-vinyl acetate copolymer (EVA) through a shaping foaming process, which can fit the human body curve well and provide comfortable support.

[0003] In addition, luminescent materials can be added to the bath pillow to make the bath pillow have a luminescent effect, which can create an atmosphere when people are taking a bath, not only attracting the attention of consumers, but also standing out from many bath products. However, in the prior art, when making luminescent materials, natural fluorescent mineral powder and ethylene-vinyl acetate copolymer are often blended and foamed. This process can make the fluorescent powder evenly distributed in the bath pillow. However, in fact, during the luminescence process, the fluorescent powder deep inside the bath pillow is difficult to absorb external energy for excitation, and it is also difficult to emit visible fluorescence, which results in a waste of fluorescent powder materials. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a luminous EVA material and a preparation method and application thereof.

[0005] The present invention provides a luminescent EVA material, which comprises, by weight, 70-80 parts of ethylene-vinyl acetate, 5-10 parts of foaming agent, 1-3 parts of cross-linking agent, 0.5-1 parts of accelerator, and 5-10 parts of modified fluorescent powder. The modified fluorescent powder comprises a magnetic fluorescent matrix and a lubricating layer coated on the surface of the fluorescent matrix. The magnetic fluorescent matrix comprises fluorescent powder and magnetic powder.

[0006] Optionally, the mass ratio of the fluorescent powder to the magnetic powder in the magnetic fluorescent matrix is ​​(8-9):1.

[0007] Optionally, the particle size of the phosphor is 1-50 μm.

[0008] Optionally, the phosphor includes one of zinc sulfide phosphor and rare earth phosphor.

[0009] Optionally, the particle size of the magnetic powder is 20-50 nm.

[0010] Optionally, the magnetic powder includes one of barium ferrite and strontium ferrite.

[0011] Optionally, the preparation method of the magnetic fluorescent matrix includes: surface activating the fluorescent powder and blending it with the magnetic powder by ball milling to obtain a mixed powder, stirring and dispersing the mixed powder in a complex solution, separating and carbonizing the mixed powder to obtain a complex powder, and magnetizing the complex powder to obtain the magnetic fluorescent matrix.

[0012] Optionally, the phosphor is stirred and dispersed in a silane solution for surface activation, wherein the solute in the silane solution includes at least one of aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane.

[0013] Optionally, the solute in the complex solution includes at least one of tartaric acid and ethylenediaminetetraacetate.

[0014] Optionally, the solvent in the complex solution includes at least one of deionized water and ethanol.

[0015] Optionally, the mass ratio of the mixed powder to the solute in the complex solution is (5-6):1.

[0016] Optionally, the mixed powder is dispersed in a complexing solution at 40-50° C. by ultrasonic and then separated.

[0017] Optionally, when the mixed powder is stirred and dispersed in the complex solution and then separated, the separation includes one of filtration separation and suction filtration separation.

[0018] Optionally, the mixed powder is stirred and dispersed in a complexing solution and then separated, and carbonized in an inert atmosphere at 600-700°C.

[0019] Optionally, the complex powder is magnetized in a magnetic field of 1.0-2.0T.

[0020] Optionally, the method for preparing the modified fluorescent powder comprises: ultrasonically dispersing the magnetic fluorescent matrix in a lubricating solution, followed by separation and drying to obtain the modified fluorescent powder.

[0021] Optionally, the solute in the lubricating solution includes butyl stearate.

[0022] Optionally, the solvent in the lubricating solution includes one of ethanol, ether and acetone.

[0023] Optionally, the mass ratio of the magnetic fluorescent matrix to the solute in the lubricating solution is 10:(0.8-1.2).

[0024] Optionally, the magnetic fluorescent matrix is ​​dispersed in the lubricating solution by ultrasound at a frequency of 20-30 kHz.

[0025] Optionally, the magnetic fluorescent matrix is ​​ultrasonically dispersed in a lubricating solution at 50-60°C.

[0026] Optionally, the magnetic fluorescent matrix is ​​dispersed in a lubricating solution by ultrasonic and then separated, and dried in a vacuum environment at 80-100° C. to obtain the modified fluorescent powder.

[0027] Optionally, the foaming agent includes at least one of azodicarbonamide and 4,4'-oxybisbenzenesulfonylhydrazide.

[0028] Optionally, the cross-linking agent includes at least one of dicumyl peroxide and 1,3-bis(tert-butylperoxyisopropyl)benzene.

[0029] Optionally, the accelerator includes at least one of zinc oxide, zinc stearate, and dimethyl silicone oil.

[0030] Optionally, the content of vinyl acetate in the ethylene vinyl acetate matrix is ​​18-40 wt.%.

[0031] In the second aspect, the present invention also provides a method for preparing any of the above-mentioned optional luminescent EVA materials, comprising the following steps: kneading ethylene-vinyl acetate at 80-100°C, adding a foaming agent, a cross-linking agent, a promoter and a modified fluorescent powder in sequence, stirring and mixing, kneading and mixing at 70-90°C, and cooling, shaping and foaming in a magnetic environment to obtain a luminescent EVA material.

[0032] In a third aspect, the present invention further provides an application of any of the above-mentioned optional luminous EVA materials, wherein the application includes an EVA mouse pad and an EVA luminous bath pillow. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0034] The present invention provides a luminous EVA material, which is made of an ethylene-vinyl acetate copolymer mixture through shaping and foaming. In fact, an ethylene-vinyl acetate body is used as a foaming matrix in the ethylene-vinyl acetate copolymer mixture. Since the ethylene-vinyl acetate body has good flexibility and water resistance, it can play a long-term use effect in a long-term humid environment, and at the same time has a good touch, and can provide a soft touch when in contact with the human body, thereby improving comfort.

[0035] Specifically, the ethylene-vinyl acetate copolymer mixture includes, by weight: 70-80 parts of ethylene-vinyl acetate, 5-10 parts of foaming agent, 1-3 parts of cross-linking agent, 0.5-1 parts of promoter, and 5-10 parts of modified phosphor. In fact, the cross-linking agent can promote the cross-linking reaction between ethylene-vinyl acetate molecules, thereby improving the overall strength and stability of the foaming material, while the foaming agent can generate gas to produce a foaming effect, the promoter can improve the decomposition efficiency of the foaming agent, and the addition of the modified phosphor can give a luminous effect.

[0036] Specifically, the modified phosphor includes a magnetic fluorescent matrix and a lubricating layer coated on the surface of the fluorescent matrix. The lubricating layer on the surface of the modified phosphor can well improve the lubricity of the modified phosphor in the foaming material, thereby facilitating the dispersion of the modified phosphor on the surface of the foaming material under the action of the magnetic field, thereby avoiding excessive distribution of the phosphor inside the material, resulting in waste and cost problems.

[0037] In fact, the magnetic fluorescent matrix includes fluorescent powder and magnetic powder. The fluorescent powder plays a role in imparting fluorescent properties. It can stimulate fluorescence in a dark light environment by absorbing energy from the outside. After the magnetic powder is compounded with the fluorescent powder, it can impart magnetism and can then move in a directed manner in a magnetic field environment, which is beneficial to the dispersion of the modified fluorescent powder in the foaming material.

[0038] In some embodiments, the preparation method of the magnetic fluorescent matrix includes: surface activating the fluorescent powder and then ball-milling and blending it with the magnetic powder to obtain a mixed powder, stirring and dispersing the mixed powder in a complex solution, separating and carbonizing the mixed powder to obtain a complex powder, and magnetizing the complex powder to obtain the magnetic fluorescent matrix.

[0039] In fact, when the phosphor is surface activated, the phosphor can be stirred and dispersed in a silane solution, so that the solute in the silane solution can surface activate the phosphor, thereby effectively increasing the number of active sites on the surface of the phosphor, which is beneficial for compounding the phosphor with the magnetic powder. Specifically, the solute in the silane solution includes at least one of aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and vinyltriethoxysilane.

[0040] In fact, by ball-milling the phosphor and magnetic powder, the particle size uniformity and dispersion uniformity of the phosphor and magnetic powder are improved, thereby facilitating the formation of a composite structure of the phosphor and magnetic powder. Specifically, the mass ratio of the phosphor to the magnetic powder is (8-9):1, which is conducive to regulating the fluorescence characteristics and balancing the overall magnetism.

[0041] In fact, when the phosphor and magnetic powder are ball-milled, the phosphor used includes one of zinc sulfide phosphor and rare earth phosphor, and the particle size of the phosphor is 1-50μm. The magnetic powder used includes one of barium ferrite and strontium ferrite, and the particle size of the magnetic powder is 20-50nm.

[0042] In some embodiments, the mixed powder is ultrasonically dispersed in a complexing solution at 40-50° C., which is conducive to the solute in the complexing solution to complex the mixed powder, thereby achieving the composite of the fluorescent powder and the magnetic powder. In addition, the treatment at a temperature of 40-50° C. is conducive to improving the reaction activity. Specifically, the solute in the complexing solution includes at least one of tartaric acid and ethylenediaminetetraacetate, and the solvent in the complexing solution includes at least one of deionized water and ethanol.

[0043] In fact, when the mixed powder is ultrasonically dispersed in the complex solution, the ultrasonic cavitation effect can effectively improve the dispersion uniformity of the mixed powder in the complex solution, which is beneficial to improve the agglomeration effect of the magnetic powder and the phosphor in the mixed powder, and is also beneficial for the solute in the complex solution to combine the magnetic powder and the phosphor to form a stable complex powder.

[0044] Specifically, when the mixed powder is ultrasonically dispersed in the complexing solution, the mass ratio of the mixed powder to the solute in the complexing solution is (5-6): 1. In fact, by adjusting the amount of solute in the complexing solution, the complexing effect of the magnetic powder and the phosphor can be effectively adjusted, and the introduction of too many impurities to cause a decrease in the content of the magnetic powder and the phosphor can be avoided while ensuring the fixation of the complex.

[0045] In some embodiments, when the mixed powder is stirred and dispersed in the complex solution and then separated, the separation process used includes filtration separation and suction filtration separation. In fact, after separation, deionized water and anhydrous ethanol can also be used to circulate and rinse the separated solids. In addition, after separation, the obtained solids are transferred to an inert atmosphere at 600-700°C for high-temperature carbonization, thereby converting the complex into a carbonized skeleton, thereby further improving the composite stability of the magnetic powder and the phosphor.

[0046] In some embodiments, when the complex powder is magnetized, the complex powder can be placed in a magnetic field environment of 1.0-2.0 T for magnetization treatment, thereby giving the magnetic powder magnetism, so that the magnetic fluorescent matrix has basic magnetism.

[0047] Specifically, the preparation method of the modified fluorescent powder includes: ultrasonically dispersing the magnetic fluorescent matrix in a lubricating solution, separating and drying, and obtaining the modified fluorescent powder. In fact, by coating the surface of the magnetic fluorescent matrix with a lubricating layer, the lubricity of the magnetic fluorescent matrix in the foaming material can be improved, thereby facilitating the movement of the magnetic fluorescent matrix in the foaming material in a magnetic environment.

[0048] In some embodiments, the solute in the lubricating solution includes butyl stearate. When butyl stearate is coated on the surface of the magnetic fluorescent matrix, it can not only improve the lubricity and distribution of the modified fluorescent powder in the foaming material, but also effectively improve the compatibility of the modified fluorescent powder in the foaming material. Through the grafting of butyl stearate and ethylene-vinyl acetate, the position stability of the modified fluorescent powder after the foaming material is foamed and fixed can be improved. Specifically, the solvent in the lubricating solution includes one of ethanol, ether, and acetone, so that butyl stearate can be effectively dissolved.

[0049] In some embodiments, when the magnetic fluorescent matrix is ​​ultrasonically dispersed in a lubricating solution, the mass ratio of the magnetic fluorescent matrix to the solute in the lubricating solution is 10:(0.8-1.2). By regulating the amount of solute in the lubricating solution, the coating thickness of the lubricating layer on the surface of the magnetic fluorescent matrix can be effectively controlled, thereby avoiding affecting the fluorescence effect of the magnetic fluorescent matrix.

[0050] In some embodiments, ultrasonically dispersing the magnetic fluorescent matrix in the lubricating solution at a frequency of 20-30 kHz for 10-15 min can effectively promote uniform dispersion of the magnetic fluorescent matrix in the lubricating solution, which is beneficial to improving the uniform coating of the solute in the lubricating solution on the surface of the magnetic fluorescent matrix.

[0051] In fact, when the magnetic fluorescent matrix is ​​ultrasonically dispersed in the lubricating solution, the magnetic fluorescent matrix can be preheated in an environment of 50-60°C, which can effectively improve the activity of the active sites on the surface of the magnetic fluorescent matrix, thereby facilitating the coating of the solute in the lubricating solution on its surface. In addition, the magnetic fluorescent matrix can also be ultrasonically dispersed in a lubricating solution at 50-60°C.

[0052] In some embodiments, the magnetic fluorescent matrix is ​​separated after ultrasonic dispersion in a lubricating solution and dried in a vacuum environment at 80-100°C to obtain a modified fluorescent powder. This can effectively improve the surface dryness of the modified fluorescent powder. In addition, deionized water and anhydrous ethanol can be used for cyclic washing after separation.

[0053] Specifically, the foaming agent includes at least one of azodicarbonamide and 4,4'-oxybisbenzenesulfonyl hydrazide; the crosslinking agent includes at least one of diisopropyl peroxide and 1,3-bis(tert-butylperoxyisopropyl)benzene; the accelerator includes at least one of zinc oxide, zinc stearate and dimethyl silicone oil; and the content of vinyl acetate in ethylene-vinyl acetate is 18-40wt.%.

[0054] At the same time, the present invention also provides a method for preparing a luminescent EVA material, comprising the following steps: after banburying ethylene-vinyl acetate at 80-100°C, adding a foaming agent, a crosslinking agent, a accelerator and a modified fluorescent powder in sequence, stirring and mixing, and then opening and mixing at 70-90°C, cooling, shaping and foaming in a magnetic environment to obtain a luminescent EVA material. In addition, the present invention also provides an application of a luminescent EVA material, which includes an EVA mouse pad and an EVA luminescent bath pillow.

[0055] Preparation Example 1

[0056] This preparation example 1 provides a method for preparing a modified phosphor, comprising the following steps:

[0057] S1. Add zinc sulfide phosphor (purchased from Shenzhen Huayu New Materials Co., Ltd., model HY-3220) to a saturated solution of aminopropyltriethoxysilane (CAS: 919-30-2, the mass ratio of zinc sulfide phosphor to aminopropyltriethoxysilane is 1:0.15) in ethyl acetate, stir and react for 2 hours in a 45°C water bath, then filter and separate, and dry in a hot air drying oven at 80°C to constant weight to obtain a surface-activated phosphor;

[0058] S2, the surface activated phosphor and the barium ferrite (BaFe 12 O 19 , CAS: 11138-11-7, purchased from Beijing Dekedaojin Technology Co., Ltd.) with a mass ratio of 8:1, and then put into a ball mill for ball milling to obtain a mixed powder;

[0059] S3, after preheating the mixed powder at 45°C for 1 hour, put it into a saturated aqueous solution of disodium diethylaminetetraacetate (the mass ratio of the mixed powder to disodium diethylaminetetraacetate is 5:1) kept in a water bath at 45°C, ultrasonically disperse it at 20kHz for 15 minutes, keep it warm for 30 minutes, filter it out and rinse it with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven at 80°C and dry it to room temperature, and then carbonize it in an atmosphere furnace at 650°C in an argon atmosphere for 2 hours to obtain a complex powder, and magnetize the complex powder in a magnetic field environment of 1.0T to obtain a magnetic fluorescent matrix;

[0060] S4. The magnetic fluorescent matrix was placed in an ethanol solution of butyl stearate (CAS: 123-95-5, purchased from Chongqing Ruiya Biotechnology Co., Ltd., with a mass ratio of magnetic fluorescent matrix to butyl stearate of 10:1) at a concentration of 1 mg / mL in a 55°C water bath, and ultrasonically dispersed at a frequency of 20 kHz and then kept warm for 2 hours. After separation by suction and circulating rinse with deionized water, the modified fluorescent powder was obtained after drying in a vacuum drying oven at 100°C to constant weight.

[0061] Preparation Example 2

[0062] This preparation example 2 provides a method for preparing a modified phosphor, comprising the following steps:

[0063] S1. Add zinc sulfide phosphor (purchased from Shenzhen Huayu New Materials Co., Ltd., model HY-3220) to a saturated solution of aminopropyltriethoxysilane (CAS: 919-30-2, the mass ratio of zinc sulfide phosphor to aminopropyltriethoxysilane is 1:0.15) in ethyl acetate, stir and react for 2 hours in a 45°C water bath, then filter and separate, and dry in a hot air drying oven at 80°C to constant weight to obtain a surface-activated phosphor;

[0064] S2, the surface activated phosphor and the barium ferrite (BaFe 12 O 19 , CAS: 11138-11-7, purchased from Beijing Dekedaojin Technology Co., Ltd.) with a mass ratio of 8:1, and then put into a ball mill for ball milling to obtain a mixed powder;

[0065] S3. After preheating the mixed powder at 45°C for 1 hour, put it into a saturated aqueous solution of disodium diethylaminetetraacetate (the mass ratio of the mixed powder to disodium diethylaminetetraacetate is 5:1) kept in a water bath at 45°C, ultrasonically disperse it at 20kHz for 15 minutes, keep it warm for 30 minutes, filter it out and rinse it with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven at 80°C and dry it to room temperature, and then carbonize it in an atmosphere furnace at 650°C in an argon atmosphere for 2 hours to obtain a complex powder, and magnetize the complex powder in a magnetic field environment of 1.0T to obtain a modified phosphor.

[0066] Preparation Example 3

[0067] This preparation example 3 provides a method for preparing a modified phosphor, comprising the following steps:

[0068] S1. Add zinc sulfide phosphor (purchased from Shenzhen Huayu New Materials Co., Ltd., model HY-3220) to a saturated solution of aminopropyltriethoxysilane (CAS: 919-30-2, the mass ratio of zinc sulfide phosphor to aminopropyltriethoxysilane is 1:0.15) in ethyl acetate, stir and react for 2 hours in a 45°C water bath, then filter and separate, and dry in a hot air drying oven at 80°C to constant weight to obtain a surface-activated phosphor;

[0069] S2. The surface activated phosphor was put into an ethanol solution of butyl stearate (CAS: 123-95-5, purchased from Chongqing Ruiya Biotechnology Co., Ltd., with a mass ratio of phosphor to butyl stearate of 10:1) in a 55°C water bath, and ultrasonically dispersed at a frequency of 20 kHz and kept warm for 2 hours. After separation by suction and circulating rinse with deionized water, the modified phosphor was obtained after drying in a vacuum drying oven at 100°C to constant weight.

[0070] Example 1

[0071] This Example 1 provides a method for preparing a luminous EVA material bath pillow, which comprises, in parts by mass: putting 70 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25 wt.%) into an internal mixer and kneading at 90°C, then adding 5 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 1 part of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 0.5 part of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 5 parts of the modified fluorescent powder prepared in Preparation Example 1 in sequence, mixing in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10 MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0072] Example 2

[0073] This Example 2 provides a method for preparing a luminous EVA material bath pillow, which comprises, in parts by mass: putting 75 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25wt.%) into an internal mixer and kneading at 90°C, then adding 10 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 2 parts of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 0.7 parts of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 8 parts of the modified fluorescent powder prepared in Preparation Example 1 in sequence, mixing and refining in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0074] Example 3

[0075] This Example 3 provides a method for preparing a luminous EVA material bath pillow, which comprises, in parts by mass: putting 80 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25 wt.%) into an internal mixer and kneading at 90°C, then adding 15 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 3 parts of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 1 part of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 10 parts of the modified fluorescent powder prepared in Preparation Example 1 in sequence, mixing in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10 MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0076] Comparative Example 1

[0077] This comparative example 1 provides a method for preparing a luminous EVA material bath pillow, which comprises, in parts by mass: putting 75 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25wt.%) into an internal mixer and mixing at 90°C, then adding 10 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 2 parts of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 0.7 parts of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 8 parts of the modified fluorescent powder prepared in Preparation Example 2 in sequence, mixing and refining in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0078] Comparative Example 2

[0079] This comparative example 1 provides a method for preparing a luminous EVA material bath pillow, which comprises, in parts by mass: putting 75 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25wt.%) into an internal mixer and mixing at 90°C, then adding 10 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 2 parts of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 0.7 parts of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 8 parts of the modified fluorescent powder prepared in Preparation Example 3 in sequence, mixing and refining in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0080] Comparative Example 3

[0081] This comparative example 3 provides a preparation method of a luminous EVA material bath pillow, which comprises, in parts by mass: putting 75 parts of ethylene vinyl acetate (purchased from McLean Reagent with item number P815475, VA content 25wt.%) into an internal mixer and mixing at 90°C, then adding 10 parts of azodicarbonamide (purchased from McLean Reagent with item number A859303), 2 parts of diisopropylbenzene peroxide (purchased from Merck Life Sciences with item number 329541), 0.7 parts of dimethyl silicone oil (purchased from Shandong Longhui Chemical Co., Ltd.) and 8 parts of zinc sulfide phosphor (purchased from Shenzhen Huayu New Materials Co., Ltd. with model number HY-3220) in sequence, mixing and mixing in an open mixer at 80°C, foaming and shaping in a magnetic environment at 180°C and 10MPa, cooling to room temperature, and polishing to obtain a bath pillow.

[0082] Performance Testing

[0083] The preparation methods provided in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare rectangular bath pillows with specifications of 20 cm in length × 10 cm in width × 5 cm in height, and the following tests were performed: compression permanent set, based on the standard described in HG / T2876, the bath pillows were compressed by 50% at 50°C and kept statically compressed for 6 hours, and the compression deformation rate was tested. The results are shown in Table 1 below; resistance to moist and hot aging, the bath pillows were aged in an environment of 75°C and 80% humidity for 12 hours, and the compression deformation rate of the bath pillows after moist and hot aging was tested, as shown in Table 1 below.

[0084] The preparation methods provided in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare rectangular bath pillows with specifications of 20 cm long × 10 cm wide × 5 cm high, respectively. The initial brightness and the brightness after 10 minutes of the bath pillows were measured based on the method described in GB / T 4070-1996 "Test Method for Performance of Phosphors", and the results are shown in Table 2 below.

[0085] Table 1 Bath pillow aging resistance test

[0086]

[0087]

[0088] Table 2 Fluorescence performance test of bath pillow

[0089] <![CDATA[Initial luminance / mcd·m -2 > <![CDATA[Luminance after 10 min / mcd·m -2 > Example 1 732.7 61.5 Example 2 749.5 68.2 Example 3 741.8 67.4 Comparative Example 1 713.2 43.8 Comparative Example 2 495.8 38.6 Comparative Example 3 482.5 37.1

[0090] As can be seen from Table 1, the use of modified phosphors that have been subjected to magnetic treatment and coated with a lubricating layer in Examples 1 to 3 can promote the modified phosphors to move to the surface of the bath pillow during the foaming process, thereby significantly improving the surface anti-aging performance of the bath pillow, and can still maintain a good compression deformation rate after wet heat aging, thereby effectively improving the performance in the bathroom. It can also be seen from Table 2 that by using the modified phosphors prepared in Preparation Example 1, the brightness retention performance of the modified phosphors can be significantly improved, and good brightness can still be maintained after 10 minutes.

[0091] It can be seen from Table 1 and Table 2 that the modified phosphor used in Comparative Example 1 is not coated with a surface lubricating layer, which makes the movement of the modified phosphor in the matrix in Comparative Example 1 hindered to a certain extent during foaming, resulting in difficulty in distributing enough modified phosphor on the surface of the bath pillow, which greatly affects the moisture and heat aging resistance of the bath pillow surface, as well as the fluorescence performance of the modified phosphor on the bath pillow surface.

[0092] It can be seen from Tables 1 and 2 that the modified phosphor used in Comparative Example 2 is not compounded with the magnetic powder, resulting in that during the foaming process of the bath pillow, the modified phosphor is still difficult to move even in a magnetic environment. This causes the modified phosphor to act more as an inorganic filler dispersed in the bath pillow, which can improve the aging resistance and mechanical properties of the bath pillow to a certain extent. However, due to the small amount of modified phosphor on the surface, the fluorescence performance of the bath pillow is greatly affected.

[0093] It can be seen from Table 1 and Table 2 that directly adding zinc sulfide phosphor in Comparative Example 3 has a similar effect to that in Comparative Example 2, but the aging resistance has decreased significantly, which means that coating the phosphor with a surface lubricating layer can improve the moisture-heat aging resistance of the bath pillow to a certain extent.

[0094] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A luminous EVA material, characterized in that: The invention comprises, by weight: 70-80 parts of ethylene vinyl acetate, 5-10 parts of foaming agent, 1-3 parts of cross-linking agent, 0.5-1 parts of accelerator and 5-10 parts of modified fluorescent powder; the modified fluorescent powder comprises a magnetic fluorescent matrix and a lubricating layer coated on the surface of the fluorescent matrix, and the magnetic fluorescent matrix comprises fluorescent powder and magnetic powder.

2. The luminous EVA material according to claim 1, characterized in that: The mass ratio of the fluorescent powder to the magnetic powder in the magnetic fluorescent matrix is ​​(8-9):1; And / or, the particle size of the phosphor is 1-50 μm; And / or, the phosphor includes one of zinc sulfide phosphor and rare earth phosphor; And / or, the particle size of the magnetic powder is 20-50 nm; And / or, the magnetic powder includes one of barium ferrite and strontium ferrite.

3. The luminous EVA material according to claim 1, characterized in that: The preparation method of the magnetic fluorescent matrix comprises: surface activating the fluorescent powder and then ball-milling and blending it with magnetic powder to obtain mixed powder, stirring and dispersing the mixed powder in a complex solution, separating and carbonizing the mixed powder to obtain complex powder, and magnetizing the complex powder to obtain the magnetic fluorescent matrix.

4. The luminous EVA material according to claim 3, characterized in that: The phosphor is stirred and dispersed in a silane solution for surface activation, wherein the solute in the silane solution includes at least one of aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and vinyltriethoxysilane; And / or, the solute in the complex solution includes at least one of tartaric acid and ethylenediaminetetraacetate; And / or, the solvent in the complex solution includes at least one of deionized water and ethanol; And / or, the mass ratio of the mixed powder to the solute in the complex solution is (5-6):

1.

5. The luminous EVA material according to claim 3, characterized in that: The mixed powder is ultrasonically dispersed in a complexing solution at 40-50°C and then separated; and / or, when the mixed powder is stirred and dispersed in the complex solution and then separated, the separation includes one of filtration separation and suction filtration separation; and / or, the mixed powder is stirred and dispersed in a complexing solution, separated, and carbonized in an inert atmosphere at 600-700° C.; And / or, the complex powder is magnetized in a magnetic field of 1.0-2.0T.

6. The luminous EVA material according to claim 1, characterized in that: The preparation method of the modified fluorescent powder comprises: ultrasonically dispersing a magnetic fluorescent matrix in a lubricating solution, and then separating and drying the magnetic fluorescent matrix to obtain the modified fluorescent powder.

7. The luminous EVA material according to claim 6, characterized in that: The solute in the lubricating solution includes butyl stearate; And / or, the solvent in the lubricating solution includes one of ethanol, ether and acetone; And / or, the mass ratio of the magnetic fluorescent matrix to the solute in the lubricating solution is 10:(0.8-1.2).

8. The luminous EVA material according to claim 6, characterized in that: The magnetic fluorescent matrix is ​​ultrasonically dispersed in the lubricating solution at a frequency of 20-30 kHz; and / or, ultrasonically dispersing the magnetic fluorescent matrix in a lubricating solution at 50-60° C.; and / or, the magnetic fluorescent matrix is ​​ultrasonically dispersed in a lubricating solution, separated, and dried in a vacuum environment at 80-100° C. to obtain a modified fluorescent powder; And / or, the foaming agent includes at least one of azodicarbonamide and 4,4'-oxybisbenzenesulfonylhydrazide; And / or, the cross-linking agent includes at least one of dicumyl peroxide and 1,3-bis(tert-butylperoxyisopropyl)benzene; And / or, the accelerator includes at least one of zinc oxide, zinc stearate, and dimethyl silicone oil; And / or, the content of vinyl acetate in the ethylene-vinyl acetate matrix is ​​18-40 wt.%.

9. A method for preparing the luminescent EVA material according to any one of claims 1 to 8, characterized in that: The following steps are involved: After ethylene-vinyl acetate is internally kneaded at 80-100° C., a foaming agent, a cross-linking agent, a accelerator and a modified phosphor are added in sequence and stirred and mixed. After open kneading and mixing at 70-90° C., the mixture is cooled and shaped in a magnetic environment to foam to obtain a luminescent EVA material.

10. An application of the luminescent EVA material according to any one of claims 1 to 8, characterized in that: The applications include EVA mouse pads and EVA luminous bath pillows.